Analisis Faktor yang Mempengaruhi Minat Nasabah Bank dalam Menggunakan Mobile Banking di Bank Syariah Indonesia Kcp Stabat Proklamasi - Tarigan, Evelyne Vagittha br; Tambunan, Khairina (Regress: Journal of Economics & Management, 2022)
Technology has a huge influence on people's lives wherever they are. One of them is the internet, the development of the internet is used by banks to develop their services. The development of services carried out by banks using technology in the form of mobile banking based on mobile phones or can be said to be phone banking, using ATM, credit cards and others has become a must for banks in Indonesia to increase their target market. At present, mobile banking is the main point and a good operational strategy for banks to improve their services. The purpose of this analysis is to find out what factors influence the interest of bank customers in using mobile banking and what strategies are used to increase customer interest and whether mobile banking can be a marketing strategy to increase customer growth at Bank Syariah Indonesia KCP Stabat Proklamasi. The method of data collection is done by asking questions or can be said to be a questionnaire.